Need for Cognition Is Positively Related to Promotion Focus and Negatively Related to Prevention Focus - Oiknine, Ashley H.; Pollard, Kimberly A.; Khooshabeh, Peter; Files, Benjamin T. (Frontiers in Psychology, 2021)
Need for cognition (NFC) and regulatory focus (RF) are important individual differences in motivation and goal pursuit. These constructs are widely used in the literature, often separately; no work has simultaneously examined the Need for Cognition scale (NCS) and Lockwood’s General Regulatory Focus Measure (GRFM). Here we explore shared theoretical underpinnings of the two constructs and assess whether they may be driven by common underlying factors. Considering purported overlaps between these scales and other constructs (e.g. personality, cognitive processes), we take a strong inference approach to test hypothesized bridges between the two measures. In a large (N=853) sample, we found NCS to be related positively to GRFM promotion and negatively to GRFM prevention scores, supporting mutual ties with BIS/BAS, intrinsic motivation, openness, and creativity. A generalized approach motivation, as well as intrinsic motivation, may thus drive both NFC and RF.